Static, dynamic and buckling analyses of 3D FGM plates and shells via an isogeometric-meshfree coupling approach. (15th August 2018) - Tan, Pengfei; Nguyen-Thanh, Nhon; Rabczuk, Timon; Zhou, Kun
Abstract: This paper develops a three-dimensional (3D) isogeometric analysis (IGA) and meshfree coupling approach to investigate the static, dynamic and buckling behaviors for plates and shells of functionally graded material (FGM). The meshfree method and IGA are coupled using the higher-order consistency condition in the physical domain so that the higher-order continuity of basis functions is guaranteed, and the topological complexity of the global volumetric parameterization for IGA to build the 3D geometry can be overcome. By employing IGA elements on the domain boundary and meshfree nodes in the interior domain, the approach preserves the advantages of the exact geometry and flexible discretization in the problem domain. Based on the coupling approach, the analyses for FGM plates and shells are carried out, and the effects of the material volume fraction, the side-to-thickness ratio and the curvature of the cylindrical shell on the deflection, natural frequency, and buckling load are investigated. The coupling approach is verified by comparing with the solutions obtained from other existing theories.